OPPORTUNITIES AND CHALLENGES OF THE LIBRARIAN PROFESSION IN THE ERA OF GLOBALIZATION - Fauzan, Ashrof Achmad (PERSPEKTIF: Journal of Social and Library Science, 2024)
Librarian is a profession that is less considered important when compared to other professions. Along with the developing technology librarians face challenges by being able to compete in the globalization era. In facing the challenges of the globalization era, librarians are required to have competence and certification and librarians must have new innovations in order to take advantage of opportunities by using information technology. In this study using the literature study method in journals that discuss the "Opportunities and Challenges of Librarians" and supplemented with previous studies. The purpose of this study is to find out what are the opportunities and challenges faced by librarians in the globalization era. At present the creation of an information society is one of the factors of information globalization which has the characteristics of information being the main strategic weapon. This is certainly a challenge for librarians in serving users, information selection must be done first. The results of this study are in facing the challenges of the globalization era, librarians must have competence and certification, think creatively, innovatively and intelligently equipped with academic knowledge and be able to master the international language in order to be able to play a role in world class librarian forum activities.